1980
DOI: 10.1002/jcu.1870080110
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of echoencephalography

Abstract: Clinical use of A- and B-mode echoencephalography in neurology, neurosurgery, and pediatrics is discussed, and some results are presented. Descriptions are given of several techniques to obtain two-dimensional echoencephalographic pictures. Two-dimensional echoencephalography can be particularly helpful with hydrocephalic babies. Recording techniques for pulsatile echoencephalography and the factors influencing the shape of cerebral echo pulsations are considered. Also, the diagnostic value of pulsatile echoen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

1981
1981
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…It was first observed in 1956 (Leksell) that the amplitude of the US signal from the cerebral midline pulsated synchronously with the cardiac cycle. Later it was observed that the cerebral hemispheres pulsated 180° out of phase with each other due to the opposing, centripetal movement of the two hemispheres (Taylor et al 1961;de Vlieger and Ridder 1959). Campbell et al (1970) described the influence of various physiological manipulations including breath holding, hyperventilation, Valsalva maneuver, and jugular vein compression on brain motion.…”
Section: Introductionmentioning
confidence: 99%
“…It was first observed in 1956 (Leksell) that the amplitude of the US signal from the cerebral midline pulsated synchronously with the cardiac cycle. Later it was observed that the cerebral hemispheres pulsated 180° out of phase with each other due to the opposing, centripetal movement of the two hemispheres (Taylor et al 1961;de Vlieger and Ridder 1959). Campbell et al (1970) described the influence of various physiological manipulations including breath holding, hyperventilation, Valsalva maneuver, and jugular vein compression on brain motion.…”
Section: Introductionmentioning
confidence: 99%
“…Ein wichtiger Grund für die Verzögerung bei der Übernahme der transkraniellen B-Mode-Sonografie (TCS) und der transkraniellen farbkodierten Duplexsonografie (TCCS) in die klinische Routine war die Konkurrenz zu den sich parallel entwickelnden CT-und MRT-Techniken, die im Gegensatz zum transkraniellen Ultraschall vollständige Gehirn-und (statische) Gefäßaufnahmen in kurzer Zeit und mit hoher Reproduzierbarkeit ermöglichen [13]. Die durch den Schädelknochen eingeschränkte Qualität der Ultraschallbilder war der Grund für die relativ lange Dominanz der eindimensionalen Echo-Enzephalografie (A-Scan) gegenüber der 2-dimensionalen Sonografie (B-Scan), sowie der konventionellen transkraniellen Dopplersonografie gegenüber der TCCS, obwohl diese früh verfügbar waren und vergleichend evaluiert wurden [14][15][16]. Anders verhält es sich bei Säuglingen, denn hier können die intrakraniellen Strukturen durch die offene Fontanelle hindurch mit hoher Bildauflösung sonografisch dargestellt werden.…”
Section: Ultrasound Imaging Modality Application In Humans (Any Clini...unclassified
“…An important reason for the delay in transferring transcranial B-mode sonography (TCS) and transcranial color-coded duplex sonography (TCCS) into clinical routine was the competition with the in-parallel evolving CT and MRI techniques that enable complete brain and (static) vasculature scans in short time and highly reproducible manner, unlike transcranial ultrasound [13]. The limitation of ultrasound image quality by the cranial bone accounted for the relatively long dominance of one-dimensional echo-encephalography (A-scan) over two-dimensional (B-mode) scan, and of conventional transcranial Doppler sonography over TCCS, despite their early availability and comparative evaluation [14][15][16]. This is different in infants in whom the intracranial structures can be visualized ultrasonically with high image resolution through open fontanelles, allowing even for the assessment of cerebral cortex and bridging veins as is elegantly demonstrated using a 14-MHz transducer in the case reported by K.H.…”
mentioning
confidence: 99%
“…Technical improvements of the last years, e. g. electronic sector scanning (Somer 1968, Freund 1973, Voigt 1975) provided a more accurate presentation, indeed, particularly of pathological intracerebral processes, but a safe interpretation only was possible by much experience. By the fast spreading of computerized axial tomography (CAT) the development of 2 dimensional ultrasound sonography slowed down (de Vlieger 1980). According to the special anatomical conditions of the newborn and the infant further experiments with Inore developed methods were carried out during the last years (Pape 1979, Horbar 1980, and correlated to CAT (Skolnik 1979).…”
Section: Introductionmentioning
confidence: 99%